Partially bio-based aromatic poly(ether sulfone)s bearing pendant furyl groups: synthesis, characterization and thermo-reversible cross-linking with a bismaleimide - Nagane, Samadhan S.; Kuhire, Sachin S.; Mane, Shivshankar R.; Wadgaonkar, Prakash P. (Polymer Chemistry, 2019)
A fully bio-based bisphenol bearing pendant furyl group, viz., 4,4'-(furan-2-ylmethylene) bis(2-methoxyphenol) (BPF) was synthesized by base-catalyzed condensation of furfural with guaiacol. New partially bio-based (co) poly(ether sulfone) s bearing pendant furyl groups were synthesized via aromatic nucleophilic substitution polycondensation of BPF and various mixtures of BPF and bisphenol-A with bis(4-fluorophenyl) sulfone in N, N-dimethylacetamide as a solvent. (Co) poly(ether sulfone) s showed inherent viscosities in the range 0.92-1.47 dL g(-1) and number average molecular weights ((M-n) over bar), obtained from GPC, were in the range 91 300-131 000 g mol(-1). (Co) poly(ether sulfone) s could be cast into tough, transparent and flexible films from chloroform solutions. (Co)poly(ether sulfone)s showed 10% weight loss in the temperature range 431-481 degrees C and DSC showed T-g in the range 179-190 degrees C. Tensile strength, Young's modulus and elongation at break, obtained from tensile testing of (co) poly(ether sulfone) s containing pendant furyl groups, were in the range 76.7-83.8 MPa, 1.02-1.18 GPa and 21.4-89.7%, respectively. Most interestingly, pendant furyl groups in (co) poly(ether sulfone) s provide reactive sites for click modification and cross-linking via Diels-Alder reaction with maleimides and bismaleimides, respectively. Crosslinked (co) poly(ether sulfone) was prepared via Diels-Alder reaction of a representative (co) poly(ether sulfone) containing pendant furyl groups with 1,1'-(methylenedi-1,4-phenylene) bismaleimide (BMI) at 60 degrees C. The formation of cross-linked poly(ether sulfone) was demonstrated by gelation tests, solubility tests and DSC. The cross-linked copoly(ether sulfone) prepared using BMI showed enhanced tensile strength and Young's modulus compared to parent copoly(ether sulfone) and was recycled two times with retention of mechanical properties.